Cover Picture: Ultrathin Surface Modification by Atomic Layer Deposition on High Voltage Cathode LiNi0.5Mn1.5O4 for Lithium Ion Batteries (Energy Technol. 2/2014). Issue 2 (February 2014) - Fang, Xin; Ge, Mingyuan; Rong, Jiepeng; Che, Yuchi; Aroonyadet, Noppadol; Wang, Xiaoli; Liu, Yihang; Zhang, Anyi; Zhou, Chongwu
<x xml:space="preserve">Abstract</x> High Energy and a Long Life—An Al2O3 coating for Li‐ion Battery Electrodes: The cover image demonstrates ultrathin Al2O3 coating by using atomic layer deposition on the high‐voltage cathode LiNi0.5Mn1.5O4 for high‐energy‐density, stable Li‐ion batteries. The ultrathin coating can protect the LiNi0.5Mn1.5O4 cathode from undesired reactions during high‐voltage cycling. At the same time, the electron path can be maintained and the extra weight added to the electrode is negligible. As described in the Full Paper by Prof. Chongwu Zhou and colleagues at the University of Southern California on page 159, superior performance can be achieved from the high‐voltage cathode of this battery configuration in both room‐temperature and high‐temperature tests.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>